Ancestors and elites : emergent complexity and ritual practices in the Casas Grandes polity - Rakita, Gordon F. M., 1971- (Archaeology of religion, 2009)
Ancestors and Elites examines the relationship between emergent social complexity and changing ritual practices at the prehispanic site of PaquimZ, Chihuahua, Mexico.